Latin American and Caribbean Regional Plan of Action on Human Settlements - UN ECLAC (UN ECLAC, 2011)
Deals with achieving social equity and alleviating urban poverty; the productivity of human settlements for improving the quality of life; improving the environment in human settlements; governability and participation; policy and management efficiency.
http://www.cepal.org/pobrezaurbana/docs/minurvi/IXForo/PlanofactiononHumanSettlements.pdf
Keywords: HUMAN SETTLEMENTS; LATIN AMERICA; CARIBBEAN